Perancangan Sistem Informasi Akuntansi Pajak Bumi Dan Bangunan (PBB) Pada Kantor Kecamatan Cileunyi Bandung Dengan Menggunakan Microsoft Visual Basic 6.0 Dan Microsoft SQL Server 2000 Berbasis Client Server - J Jayinudin (Labkat Press KA FTIK UNIKOM, 2017)
Conditions that occur in the calculation of land tax and building in the Cileunyi District Office already using is based on Law No. 12 of 1994, but in performing procedures tax such as making tax monthly and annual reports are still using Microsoft Office Excel 2007. To the problems, then writer take the title: